Erratum: Hubungan Daya Ledak Otot Tungkai Dengan Kecepatan Lari Jarak Pendek 100 Meter - Raffly Henjilito (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.540 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.